A new alternative to cosmetics preservation and the effect of the particle size of the emulsion droplets on preservation efficacy. (5th April 2016) - Fang, B.; Yu, M.; Zhang, W.; Wang, F.
Abstract: Objective: This study describes a new alternative combination preservative containing caprylyl glycol, phenethyl alcohol and glyceryl caprylate and investigates the effects of the particle size of the emulsion droplet on the anti‐microbial activity of the said blend in the formulation. Methods: The anti‐microbial activity of the ingredients and the blend were determined via MIC, MBC, MFC and fractional inhibitory concentration (FIC) determination using the broth microdilution method. The blend inhibited the micro‐organism contamination of the oil‐in‐water emulsion, and its performance was affected by the particle size of the emulsion droplet, as shown by the in vitro microbial challenge test. Results: Results show that the MIC/MBC/MFC values of the blend were lower than those of any of the ingredients used alone. Any two of the ingredients presented no antagonistic activities against all the tested micro‐organisms, and synergism or additive effects were also observed. The challenge test also showed that the action of the blend against bacteria and yeast was only 0.3% and 0.2%, respectively, and mould was completely inhibited at 1.4%, meeting the requirements of the PCPC and European Pharmacopoeia. The results showed that anti‐microbial activity was gradually enhanced when the particle size of the emulsion droplets increased significantly in the range of 100–900 nm. A positive correlation was found between anti‐microbial activity and particle size. Conclusion: The synergistic performance of caprylyl glycol, phenethyl alcohol and glyceryl caprylate and the anti‐microbial activity of their blend suggest that their combination is effective and exhibits broad‐spectrum anti‐microbial activity. Furthermore, the results show a positive correlation between the anti‐microbial activity of the preservative and the particle size of the emulsion droplets in the range of 100–900 nm, when the same concentration of the blend is used in the same formulation. The particle size of the emulsion droplets is demonstrated to be a newly discovered factor that influences the preservation of cosmetic products.